CAPABILITIES OF THE EDUCATION AND CULTURE OFFICE IN HERITAGE TOURISM MANAGEMENT IN THE CITY OF SUKABUMI - Utari, Suci Dwi; Purwanti, Dian; Mulyadi, Andi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to determine the capability of the Office of Education and Culture in managing heritage tourism in Sukabumi City. The research method in this study uses a qualitative research type, with 4 informants through observation, interview, and documentation data collection techniques. The results found that overall, the management of heritage tourism in Sukabumi City can be said to be good and quite effective. However, in practice, a holistic approach is needed that includes better coordination between institutions, increased promotional efforts and legal improvements, as well as active community involvement to ensure more effective preservation and promotion of cultural heritage. In addition, researchers found that the biggest challenges faced in the management of cultural heritage in Sukabumi City include legal aspects, budgeting, and conflicts of interest between institutions. The importance of a strong legal stipulation related to cultural heritage was highlighted. Meanwhile, cooperation between institutions such as the Culture Office, Tourism Office, and Archives Office needs to be strengthened to better promote destinations and maintain cultural heritage.